The branched chains and branching degree of exopolysaccharides affecting the stability of anammox granular sludge. (1st July 2020) - Wang, Shuai; Liu, Lijuan; Li, Hanxiang; Fang, Fang; Yan, Peng; Chen, Youpeng; Guo, Jinsong; Ma, Tengfei; Shen, Yu
Abstract: The effect of extracellular polysaccharides on the structural stability of granular sludge is widely recognized, and determining their mechanism of action on the stability of granules remains challenging. Herein, enzymatic experiments were used to systematically study the stability changes and internal mechanisms of anammox granular sludge following hydrolysis of extracellular proteins and polysaccharides (PS). The results revealed that the selective hydrolysis of the proteins hardly affected the stability of the granules, while the hydrolysis of the PS branched chains caused the granules to disintegrate. The hydrolysis of the PS chains in the EPS matrix decreased the degree of branching, width and height via nuclear magnetic resonance (NMR) spectroscopy and atomic force microscopy (AFM), and these parameters are closely related to granular stability. Moreover, scanning electron microscopy (SEM) showed a large number of pores and cracks on the granules, bacterial adhesion decreased, and the EPS adhered to the surface of the granules dissolved. The changes in the gel characteristics of the granules were studied by rheology, and the mechanical strength and viscosity of the granular sludge decreased. For the surface characteristics of granules, the zeta potential and hydrophobicity both decreased, revealing that changes in the branched-chain configuration of the PS and the degree of branching caused granular disintegration. Spectral analysis showed that the hydrolysis of the branch points and the branched glycosides of PS led to a higher proportion of hydrophilic and electronegative groups in the EPS matrix, which hindered bacterial aggregation and reduced anammox granule stability. This investigation clarifies the impact of the branched-chain configuration of the PS and their degree of branching on anammox granule stability, which will promote the further application of anammox granules. Graphical abstract: Image 1 Highlights: The total protein and polysaccharide is not a parameter to the granular stability. Changes of polysaccharide chains were characterized by AFM. Polysaccharide branched chains affected granular mechanical strength and viscosity. Polysaccharide branched chains affected granular zeta potential and hydrophobicity. Granular stability and polysaccharide branched structure is well correlated.